Utilization Of Big Data in Educational Technology Research - Ninda Lutfiani; Lista Meria (Pandawan Sejahtera Indonesia, 2022)
This research aims to exploit the role and contribution of big data in normal-age learning paradigms that require online learning that was initially conducted face-to-face. Educational technology research includes research areas that require changes in learning strategies. This includes the use of technology currently occurring during the COVID-19 virus pandemic to transform face-to-face learning online. Use big data to develop learning strategies (procedures) to solve problems/facilitate learning. The use of big data can contribute to the study of education in general and educational technology in particular. Methodologies used include the analysis and potential implementation of big data in the field of educational technology research by conducting literature survey analyses. The data obtained and used are in the form of local and international journals related to the implementation of big data in the world of educational technology research. The development of technology research applications based on big data makes it easier for researchers to see the possibilities and problems of individual students. Based on this data, researchers can monitor and evaluate students, teachers, materials, and learners. The data can be used to prepare future research efforts.